2009
DOI: 10.2106/jbjs.h.00345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Unrepaired Fracture of the Ulnar Styloid Base on Outcome After Plate-and-Screw Fixation of a Distal Radial Fracture

Abstract: An unrepaired fracture of the base of the ulnar styloid does not appear to influence function or outcome after treatment of a distal radial fracture with plate-and-screw fixation, even when the ulnar fracture was initially displaced >or=2 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 23 publications
(30 reference statements)
3
81
1
9
Order By: Relevance
“…They concluded that ulnar styloid fracture with displacement more than 2 mm is risk factor for DRUJ instability. Souer et.,al 15 in a matched cohort study of patients with or without ulnar styloid base fracture (76 in each group) having distal radius volar plating and followed up for 24 months, found no measurable differences in motion, strength, pain, or functional scores based on presence of styloid fracture or on initial displacement of more or less than 2 mm. The authors did not specifically assess DRUJ instability before or after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…They concluded that ulnar styloid fracture with displacement more than 2 mm is risk factor for DRUJ instability. Souer et.,al 15 in a matched cohort study of patients with or without ulnar styloid base fracture (76 in each group) having distal radius volar plating and followed up for 24 months, found no measurable differences in motion, strength, pain, or functional scores based on presence of styloid fracture or on initial displacement of more or less than 2 mm. The authors did not specifically assess DRUJ instability before or after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Because of its anatomic proximity to the triangular fibrocartilage complex, fracture of the ulnar styloid at its base has been postulated to cause DRUJ instability [12,28,33,37]. However, well-designed studies consistently denied the association between symptomatic DRUJ instability and the ulnar styloid fracture in distal radius fractures [15,35,39,44]. Recently widening of the DRUJ gap was identified as an independent risk factor for DRUJ instability in distal radius fractures [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, it still is unclear whether the displaced ulnar styloid fractures cause pain and instability at the DRUJ in patients with distal radius fractures [34,40,44]. One study suggested that stable internal fixation of distal radius fractures results in a stable DRUJ after bony healing regardless of the presence of substantially displaced, unrepaired ulnar styloid fractures [39], whereas two studies [15,35] reported no differences in the wrist function between patients with unrepaired ulnar styloid fractures and those without ulnar styloid fractures. In addition, factors other than ulnar styloid fractures have been investigated only rarely in distal radius fractures for DRUJ instability.…”
Section: Introductionmentioning
confidence: 99%
“…1). Eight studies met our inclusion criteria; however, two studies did not report sufficient data to be included in the meta-analysis leaving six studies available for meta-analysis [24][25][26][27][28][29][30]. These studies included a total of 135 patients in the union group and 230 in the nonunion group.…”
Section: Literature Searchmentioning
confidence: 99%
“…Mentzel and colleagues reported a better residual function if the USP fracture unites [24]. Others found that nonunion of the ulnar styloid did not affect functional outcome or pain following volar plate fixation of a DRF [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%